Stellar encounters in the context of outburst phenomena - Forgan, Duncan; Rice, Ken (Monthly notices of the Royal Astronomical Society, 2010)
Young stellar systems are known to undergo outbursts, where the star experiences an increased accretion rate, and the system's luminosity increases accordingly. The archetype is the FU Orionis (FU Ori) outburst, where the accretion rate can increase by three orders of magnitude (and the brightness of the system by five magnitudes). The cause appears to be instability in the circumstellar disc, but there is currently some debate as to the nature of this instability (e.g. thermal, gravitational, magneto-rotational). This paper details high-resolution smoothed particle hydrodynamics (SPH) simulations that were carried out to investigate the influence of stellar encounters on disc dynamics. Star–star encounters (where the primary has a self-gravitating, marginally stable protostellar disc) were simulated with various orbital parameters to investigate the resulting disc structure and dynamics. Crucially, the simulations include the effects of radiative transfer to realistically model the resulting thermodynamics. Our results show that the accretion history and luminosity of the system during the encounter display many of the features of outburst phenomena. In particular, the magnitudes and decay times seen are comparable to those of FU Ori. There are two caveats to this assertion: the first is that these events are not expected to occur frequently enough to explain all FU Ori or EX Lupi; the second is that the inner discs of these simulations are subject to numerical viscosity, which will act to reduce the accretion rate (although it has less of an effect on the total mass accreted). In short, these results cannot rule out binary interactions as a potential source of some FU Ori-esque outbursts.